Development of Inclusion Through Minority-Conscious Tourism in The Madura Religious Tourism Area - Prastiwi, Merlia Indah; Wardhana, Indra Jaya Kusuma (Journal of Contemporary Sociological Issues, 2024)
In carrying out sustainable development, paying attention to many aspects is necessary. This article explores the aspect of justice for the entire community, which is one of the characteristics of religious tourism branding, which can provide access to the entire community to feel comfortable and safe when traveling and create significant growth in the creative economy of the surrounding community. Madura is generally known as a religious area that emphasizes religious values. In religious values, God never differentiates between his people. The research used a qualitative approach with the interpretive method where informants experienced an in-depth interview. The research finding described that in its development, Madura religious tourism should pay attention not only to economic aspects but also to the involvement of social justice in providing opportunities for people with disabilities to access the religious facilities and religious tourism they have. Together with the tourism department, researchers are trying to provide suggestions and strategies for the sustainability of religious tourism development that prioritizes aspects of religious branding and justice for every congregation. With increasing attention to the rights of people with disabilities in religious tourism, the image and branding will increase to attract the wider community to increasingly visit tourism in Madura in general and religious tourism in Sumenep in particular. Development focusing more on the tourism sector and the creative economy should not marginalize people with disabilities as part of the development object. Therefore, inclusion-friendly tourism development needs to be an input for related agencies and local governments to uphold aspects of social justice among fellow humans. Keywords: Inclusion development, Madura, Minority-conscious tourism, Religious tourism